Finite Element Analysis of Air Flow and Temperature Distribution on Surface of a Circular Obstacle with Resistance and Orientation of Screen - Abid A. Memon; M. Asif Memon; Aisha M. Alqahtani; Kaleemullah Bhatti; Kamsing Nonlaopon; Ilyas Khan; Mulugeta Andualem (Journal of Mathematics)
Nonisothermal flow through the rectangular channel on a circular surface under the influence of a screen embedded at the middle of a channel at angles θ is considered. Simulations are carried out via COMSOL Multiphysics 5.4 which implements the finite element method with an emerging technique of the least square procedure of Galerkin’s method. Air as working fluid depends upon the Reynolds number with initial temperature allowed to enter from the inlet of the channel. The nonisothermal flow has been checked with the help of parameters such as Reynolds number, angle of the screen, and variations in resistance coefficient. The consequence and the pattern of the velocity field, pressure, temperature, heat transfer coefficient, and local Nusselt number are described on the front surface of the circular obstacle. The rise in the temperature and the flow rate on the surface of the obstacle has been determined against increasing Reynolds number. Results show that the velocity magnitudes are decreasing down the surface and the pressure is increasing down the surface of the obstacle. The pressure on the surface of the circular obstacle was found to be the function of the y-axis and does not show any impact due to the change of the resistance coefficient. Also, it was indicated that the temperature on the front circular surface does not depend upon the orientation of the screen and resistance factor. The heat transfer coefficient is decreasing which indicates that the conduction process is dominating over the convection process.